Histological mapping of porcine carotid arteries - An animal model for the assessment of artificial conduits suitable for coronary bypass grafting in humans - Tomášek, Petr; Tonar, Zbyněk; Grajciarová, Martina; Kural, Tomáš; Turek, Daniel; Horáková, Jana; Pálek, Richard; Eberlová, Lada; Králíčková, Milena; Liška, Václav (Annals of anatomy, 2020)
BACKGROUND: Using animal models in experimental medicine requires mapping of their anatomical variability. Porcine common carotid arteries (CCA) are often preferred for the preclinical testing of vascular grafts due to their anatomical and physiological similarity to human small-diameter arteries. Comparing the microscopic structure of animal model organs to their human counterparts reveals the benefits and limitations of translational medicine. METHODS: Using quantitative histology and stereology, we performed an extensive mapping of the regional proximodistal differences in the fractions of elastin, collagen, and smooth muscle actin as well as the intima-media and wall thicknesses among 404 segments (every 1 cm) of porcine CCAs collected from male and female pigs (n = 21). We also compared the microscopic structure of porcine CCAs with segments of human coronary arteries and one of the preferred arterial conduits used for the coronary artery bypass grafting (CABG), namely, the internal thoracic artery (ITA) (n = 21 human cadavers). RESULTS: The results showed that the histological structure of left and right porcine CCA can be considered equivalent, provided that gross anatomical variations of the regular branching patterns are excluded. The proximal elastic carotid (51.2% elastin, 4.2% collagen, and 37.2% actin) transitioned to more muscular middle segments (23.5% elastin, 4.9% collagen, 54.3% actin) at the range of 2-3 centimeters and then to even more muscular distal segments (17.2% elastin, 4.9% collagen, 64.0% actin). The resulting morphometric data set shows the biological variability of the artery and is made available for biomechanical modeling and for performing a power analysis and calculating the minimum number of samples per group when planning further experiments with this widely used large animal model. CONCLUSIONS: Comparison of porcine carotids with human coronary arteries and ITA revealed the benefits and the limitations of using porcine CCAs as a valid model for testing bioengineered small-diameter CABG vascular conduits. Morphometry of human coronary arteries and ITA provided more realistic data for tailoring multilayered artificial vascular prostheses and the ranges of values within which the conduits should be tested in the future. Despite their limitations, porcine CCAs remain a widely used and well-characterized large animal model that is available for a variety of experiments in vascular surgery.
Keywords: tkáňové inženýrství; arteriae carotides; Cadaver; imunohistochemie; Blood Vessel Prosthesis; srdce; lidé; koronární bypass; prasata; cévní protézy; Models, Animal; mužské pohlaví; Female; mrtvola; Immunohistochemistry; Pilot Projects; modely u zvířat; Male; ženské pohlaví; Coronary Artery Bypass; Heart; Animals; Humans; zvířata; pilotní projekty; Tissue Engineering; Carotid Arteries; Swine